The Cryptococcus neoformans Transcriptome at the Site of Human Meningitis - Yuan Chen (American Society for Microbiology, 2014)
ABSTRACT Cryptococcus neoformans is the leading cause of fungal meningitis worldwide. Previous studies have characterized the cryptococcal transcriptome under various stress conditions, but a comprehensive profile of the C. neoformans transcriptome in the human host has not been attempted. Here, we extracted RNA from yeast cells taken directly from the cerebrospinal fluid (CSF) of two AIDS patients with cryptococcal meningitis prior to antifungal therapy. The patients were infected with strains of C. neoformans var. grubii of molecular type VNI and VNII. Using RNA-seq, we compared the transcriptional profiles of these strains under three environmental conditions (in vivo CSF, ex vivo CSF, and yeast extract-peptone-dextrose [YPD]). Although we identified a number of differentially expressed genes, single nucleotide variants, and novel genes that were unique to each strain, the overall expression patterns of the two strains were similar under the same environmental conditions. Specifically, yeast cells obtained directly from each patient’s CSF were more metabolically active than cells that were incubated ex vivo in CSF. Compared with growth in YPD, some genes were identified as significantly upregulated in both in vivo and ex vivo CSF, and they were associated with genes previously recognized for contributing to pathogenicity. For example, genes with known stress response functions, such as RIM101, ENA1, and CFO1, were regulated similarly in the two clinical strains. Conversely, many genes that were differentially regulated between the two strains appeared to be transporters. These findings establish a platform for further studies of how this yeast survives and produces disease. IMPORTANCE Cryptococcus neoformans, an environmental, opportunistic yeast, is annually responsible for an estimated million cases of meningitis and over 600,000 deaths, mostly among HIV-infected patients in sub-Saharan Africa and Asia. Using RNA-seq, we analyzed the gene expression of two strains of C. neoformans obtained from the cerebrospinal fluid (CSF) of infected patients, thus creating a comprehensive snapshot of the yeasts’ genetic responses within the human body. By comparing the gene expression of each clinical strain under three conditions (in vivo CSF, ex vivo CSF, and laboratory culture), we identified genes and pathways that were uniquely regulated by exposure to CSF and likely crucial for the survival of C. neoformans in the central nervous system. Further analyses revealed genetic diversity between the strains, providing evidence for cryptococcal evolution and strain specificity. This ability to characterize transcription in vivo enables the elucidation of specific genetic responses that promote disease production and progression.